The Effect of Spiritual Quotient, Affective Commitment, and Perceived Organizational Support towards Work Engagement and Employee Performance of the Teacher in Langke Rembong District, Manggarai Region - Herman Yosef Arisutama Atom; Tri Andjarwati; I Dewa Ketut Raka Ardiana (International Journal of Economics (IJEC), 2023)
This study aims to determine the effect of spiritual quotient, affective commitment, and perceived organizational support towards work engagement and employee performance of the teacher in Langke Rembong District, Manggarai Region. In this study, the researchers used purposive sampling technique to determine the research sample. The sample used was 80 civil servant teachers in Langke Rembong District, Manggarai Region. This research used quantitative approach and PLS-SEM method for data analysis. Data was collected by distributing questionnaires and analyzed descriptively by conducting validity, reliability, and path analysis tests by using Smart-PLS 4.0 software. The results showed that spiritual quotient (X1) affects work engagement (Z), spiritual quotient (X1) affects employee performance (Y), affective commitment (X2) affects work engagement (Z), affective commitment (X2) affects employee performance (Y), perceived organizational support (X3) has no effects on work engagement (Z), perceived organizational support (X3) affects employee performance (Y) and work engagement (Z) affects employee performance (Y).